4 - Editing African Social Science: Some reflections and suggestions - Jeffrey Lever, (Africa Media Review, 2006)
The present essay examines the challenges and promises of academic publishing in Africa, and offers very useful tips for getting one’s ideas in print. The role of the copy editor in this process is also examined.